Line-of-Sight Velocity As a Tracer of Coronal Cavity Magnetic Structure - Bąk-Stȩślicka, Urszula; Gibson, Sarah E.; Chmielewska, Ewa (Frontiers in Astronomy and Space Sciences, 2016)
We present a statistical analysis of 66 days of observations of quiescent (non-erupting) coronal cavities and associated velocity and thermal structures. We find that nested rings of LOS-oriented velocity are common in occurrence and spatially well correlated with cavities observed in emission. We find that the majority of cavities possess multiple rings, and a range in velocity on the order of several $km/sec$. We find that the tops of prominences lie systematically below the cavity center and location of largest Doppler velocity. Finally, we use DEM analysis to consider the temperature structure of two cavities in relation to cavity, prominence, and flows. These observations yield new constraints on the magnetic structure of cavities, and on the conditions leading up to solar eruptions.